Microstructure, Deformation Characteristics and Energy Analysis of Mudstone under Water Absorption Process - Zheyuan Feng; Qi Xu; Xinyu Luo; Ruyu Huang; Xin Liao; Qiang Tang (Energies, 2022)
In geological engineering, a series of safety problems caused by expansive mudstone are common, such as slope instability and roadbed up-arch. In this paper, the mineral composition of mudstones in the Xining area was analyzed by X-ray diffraction (XRD), and the microstructural and morphological changes of mudstones after water absorption were observed by scanning electron microscopy (SEM) test to analyze the internal factors and microstructural evolution patterns of water absorption and swelling of mudstones. Based on the microstructural units, the mudstones were defined into two categories, one is N-type mudstone with flat sheet-like stromatolite units, and the other is SN-type mudstone with more clastic particle units. Water absorption experiments were conducted on the rock samples to study the microstructure of these two types of mudstones under different water absorption conditions. The pore characteristics of the mudstones were analyzed by using Image-Pro Plus to reveal the water absorption mechanism. The results show that the pore area of N-type mudstone is smaller, as well as the distribution of pore diameter. The pore area of N-type mudstone develops rapidly, in the early stage of water absorption, lots of pores are produced, and the pore area of SN-type mudstone shows an overall decreasing trend. The pore area and the number of SN-type mudstones are at a low level after full water absorption. Under the condition of full immersion, water enters the pores rapidly and soluble salts are dissolved in large quantities. The change of water absorption rate of mudstone with time can be divided into the stage of sudden increase, decrease and stability of water absorption rate. Then, based on the stress theory, the relationship between the macroscopic expansion process and the microstructure of mudstone was analyzed. Finally, the energy basis of mudstone water absorption is discussed. In the swelling of mudstone, the energy gradually turns into swelling strain energy.